2016
DOI: 10.1002/fsn3.333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different fermentation processes for use by small cocoa growers in mexico

Abstract: The aim of this research was to evaluate four different cacao (Theobroma cacao L.) fermentation conditions and their effect on fermented bean quality, in order to be able to recommend the most suitable condition to producers in the municipality of Huimanguillo, Tabasco, Mexico. Fermentations were carried out in square wooden boxes with capacity for 1000, 300, and 100 kg of fresh beans, as well as a rotary drum with capacity for 500 kg thereof. The fermentation process was carried out for 7 days, and the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 23 publications
(59 reference statements)
4
20
0
1
Order By: Relevance
“…During fermentation, flavor and aroma precursors develop and pigments are degraded by the action of enzymes such as invertases, glycosidases, proteases, and polyphenol oxidase. Fermentation influences the compounds such as reducing sugars, peptides, and amino acids, which are converted into flavor and smell profiles during the drying and roasting steps of chocolate processing [6]. Tea is a rich source of several flavonoid compounds that are responsible for its distinctive taste and color along with various health benefits.…”
Section: Fermentation In the Preparation Phase Fermentation Of The Fimentioning
confidence: 99%
“…During fermentation, flavor and aroma precursors develop and pigments are degraded by the action of enzymes such as invertases, glycosidases, proteases, and polyphenol oxidase. Fermentation influences the compounds such as reducing sugars, peptides, and amino acids, which are converted into flavor and smell profiles during the drying and roasting steps of chocolate processing [6]. Tea is a rich source of several flavonoid compounds that are responsible for its distinctive taste and color along with various health benefits.…”
Section: Fermentation In the Preparation Phase Fermentation Of The Fimentioning
confidence: 99%
“…The oxidation of alcohol is an exothermic process that causes the temperature of the fermenting mass to be increased, reaching temperatures higher than 45°C (De Vuyst and Weckx, 2016;Gutiérrez, 2017). However, such temperatures above 45°C were reported for large-scale fermentation at least 100 kg of cocoa as shown during fermentations performed by Hernández-Hernández et al (2016), Lagunes-Gálvez et al (2007, and Papalexandratou et al (2019). In the case of small-scale cocoa fermentations, it has been reported that the maximum temperature reached is around or less than 45°C.…”
Section: Temperature and Ph During Small-scale Cocoa Bean Fermentation Protocolsmentioning
confidence: 99%
“…Increased fermentation air temperature will occur optimally if the fermentation air needs are met properly. It is known that during the fermentation process there is generally a temperature change between 25-52℃ [10]- [12]. Aeration factor is the main thing that must be considered in a good fermenter design to optimize the physical aspects of the fermentation process [5].…”
Section: Introductionmentioning
confidence: 99%